Práticas de governança corporativa: uma investigação sobre os conselhos de administração nas empresas listadas no novo mercado da BM&FBOVESPA - Said, Yvelise Lima Benevides (2010)
The changes in the negotiations between companies and the development of capital markets driving the development of corporate governance practices for companies. The Board of Directors, a key mechanism of corporate governance, is entrusted with the responsibility for ensuring that the balance of interests and scope of the company's goals. This dissertation aims to analyze the corporate governance exercised by the Boards of Directors of companies listed on the New Market of BM&FBOVESPA, in respect to what is recommended by IBGC (2009). This research is descriptive, with qualitative approach. The study compared the recommendations for boards of directors of the main recommendations and codes national and international that what is advocated by IBGC (2009), confirming, in part, the presupposition that they have similar practices. It used a questionnaire to investigate the practices adopted, which was segmented into 13 topics: duties and responsibilities; composition and quality; deadline mandate; participation in other boards and committees; segregation of duties; number and class of directors; evaluation of board of directors and advisors; evaluate the CEO and of the executive board; board interlocking; remuneration of board members; bylaws of the board; consulting board and committees; and relationship of the board with the other agents / agencies. The results indicate that, although some recommendations in the IBGC (2009) are met, others considered relevant are not yet covered in the responses received from enterprises, for example, the evaluation of the board of directors and the number and class of directors, which calls attention to the role of boards of directors in these companies.